PHILOSOPHICAL DETERMINANTS OF DETERMINATION OF OFFENCES - Ikromjonov Jamshidbek Bahtiyorjon o‘g‘li (Sciental Journals Publishing, 2025)
This study analyzes the role of philosophical determinants in the identification of offenses. The moral criteria of the human mind, free will, and the formation of social consciousness are considered as important factors in the evaluation of legal behavior. Based on the relationship between law and morality, social justice and individual freedom, a profound philosophical approach to the essence of the offense is proposed.
Keywords: Offense, philosophical determinants, morality, social consciousness, freedom, justice, legal consciousness.